ASUPAN KARBOHIDRAT DAN LEMAK PADA DIABETESI TIPE II YANG RAWAT JALANDI PUSKESMAS TOMBATU - Rudolf B. Purba; Nita R. Momongan; Shintya Monolimay (Jurnal GIZIDO, 2015)
Diabetes mellitus (DM) is a collection of symptoms in a person due to impaired body incontrolling blood sugar levels. Number of patients with diabetes mellitus from 8.4 millionin 2004 to about 21.3 million in 2030. This was due to the intake of food that has been inexcess of the needs, especially the intake of carbohydrates and fats. The study aims todetermine the intake of carbohydrates and fats consumed by people with diabetesmellitus (diabetes). This type of research is descriptive. This study was conducted in Mays/d June 2015. Sampling using consecutive sampling with a sample of 30 people.Carbohydrate and fat intake data was obtained using a 24 hour recall form. Examinationof blood sugar levels is done by using the blood sugar measuring device Autochek. Thedata is processed carbohydrate and fat intake using nutry survey and analyzed innarrative form. The results showed that carbohydrate intake of 30 samples averaged 164grams per day with less intake category as much as 93%, more intake category as muchas 7%. While fat intake of 30 samples averaged 42.9 grams per day with less intakecategory and more each as much as 50%. On average the eating habits of people withdiabetes do not consume enough carbohydrates but high in fat